Multilayered model of speech - Chistyakov,Andrey (PeerJ Preprints, 2017)
Today there are no grammar systems, which allow the creation of a fundamentally new word and concept. All existing grammar systems only work by referring to previously chosen terms, on the bases of which all definitions are created. Implementation of operation on grammar systems are introduced for creation of new terms. The main prerequisite of the research was the rejection of finding a universal solution, which is true for any person. Instead of this, all people were divided into groups according MBTI classification. Each group was expected to have uniform perception of new knowledge. Assessment has been conducted to each group. A mathematical model was created as result of the communication. The scheme of dividing words and sentences into components are shown in the first section of the article. The second section shows a notation construction from the components and the notation packing in memory. The third section shows the ability for conscious memory access (self-action and self-image). As a result, the model of human speech was structured, in where it is possible to create new terms from new knowledge independently.
Keywords: Natural language processing; Speech recognition; Artificial Intelligence